Goals of Parents Whose Infant Is in the Neonatal Intensive Care Unit: An Explorative Study. (December 2020) - Fucile, Sandra; Samson, Jessica; Rockley, Jeremy; Dow, Kimberly
Abstract : Background: The aim of many neonatal intensive care units (NICU) today is to promote a family-centered practice that addresses parental concerns and needs. However, the specific goals of parents are often unaddressed by the healthcare team. The aim of this study was to understand the goals of parents whose infant was in the NICU to enhance collaboration and communication between parents and health professionals. Methods: A written questionnaire was disseminated to parents whose infant was in the NICU at the Kingston Health Sciences Centre. A thematic analysis of the goals was completed to identify key emergent themes and their implications. Results: A total of 23 questionnaires were disseminated to parents and 13 (57%) were returned. Returned questionnaires were most often completed by the mother (n = 9, 70%), and a total of 40 goals were recorded. Three key emergent themes were identified, which included feeding and weight gain, eliminating medical equipment, and successful hospital discharge. Implications for Practice: Understanding the goals of parents whose infant was in the NICU can enhance communication between parents and their healthcare team, thus aiding the implementation of a family-centered practice. Implications for Research: Future larger sample sizes studies across several NICUs would increase the generalizability of results and garner a larger volume of data to establish significant trends between specific infant and parent demographic data and the associated goals.